Formulation and In Vitro, In Vivo Evaluation of Mucoadhesive Buccal Tablet of Felodipine - Balamurugan, K. (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: This study aims to formulate and evaluate the mucoadhesive buccal tablets of felodipine (FD) by direct compression to improve the drug release and subsequently oral bioavailability. Materials and Methods: The pure drug FD and excipient were obtained from manufacturing industries. The powder blend formulation studies, moisture absorption study, residence time, ex vivo permeation, and in vivo drug release were studied. Results and Discussion: The results for powder flow properties was found to be within the limits, moisture absorption study was between 20.21% and 34.05% v/w residence time 7.45 Â± 0.10 (h) ex vivo permeation 97.83 Â± 0.52% and in vivo drug release was extended till 24 h and area under the curve 880.59 mg/h/l with an Tmax at 8 h. Conclusion: The region in which it will remain in contact were perfectly done with appropriate evaluation techniques (Residence time), the moisture absorption study was carried out to check how much moisture the tablet can absorbed to release the drug and was found satisfactory. The ex vivo permeation study was performed by Franz diffusion cell to check the drug permeation through buccal mucosa. The in vivo studies were performed on New Zealand rabbits and can be concluded that the drug release from the formulated F6 was better than the marketed application programing interface.